Compensatory Belief in Health Behavior Management: A Concept Analysis - Zhao, Kang; Xu, Xinyi; Zhu, Hanfei; Xu, Qin (Frontiers in Psychology, 2021)
Purpose This study aimed to identify the exact definition of the concept of compensatory belief (CB) and to help clinicians and caregivers to distinguish patients who tend to form such beliefs. Methods This study is a conceptual analysis based on the strategy of Walker and Avant (2014). We retrieved studies from existing literature using databases such as PubMed, CINAHL, Wiley, and Web of Science, and extracted information from the results. No date limitations were applied. Results A total of 35 articles were sourced for data extraction. The identified attributes of CB were as follows: cognitive coping strategy, pleasure without guilt, compensatory behaviors, automatic motivated self-regulatory process, and implicit cognition. The observed antecedents were: failure to resist desire, reluctance, a conflicting motivational state, seeking appropriate balance, and self-image maintenance. The consequences of CB were lower health-related intentions, justification of unhealthy choices, relief from cognitive dissonance, continued existence of conflict feeling, and poor long-term health. Conclusion Compensatory belief stems from motivational dissonance or confliction. Despite causing feelings of pleasure and relief, it can negatively impact long-term health. Although CB is crucial to establish healthy behaviors, it is easily ignored in medical work.